The effects of two aerobic training intensities on the aerobic and anaerobic power of prepubescent boys - Mascarenhas, Luís Paulo Gomes; Stabelini Neto, Antonio; Vasconcelos, Italo Quenni Araújo de; Smolarek, André de Camargo; Bozza, Rodrigo; Ulbrich, Anderson Zampier; Campos, Wagner de (Brazilian journal of physical education and sport, 2008)
The purpose of this study was to verify the effects of two aerobic training intensities on the body composition, aerobic and anaerobic power of prepubescent boys. The sample were constituted by 35 children, 12 boys performed aerobic training at 70% of reserve heart rate; 12 did boys realized aerobic did training at 50% of reserve heart rate; and 11 boys served as a control group. It was measured total body mass, stature, and percentage of body fat. Physical activity level was estimated using a questionnaire proposed by Bouchard. The aerobic power was measured by the 20 m shuttle-run test and anaerobic power by the Wingate test. Observing the results, with the more intense aerobic training (70% of HR reserve), there was no change in the percentage of fat and increase in anaerobic power, however, there was an increased in aerobic power (p < 0.05). Independent of the physical activity levels, only the high intensity training was capable of elevating the aerobic power of prepubescent boys.